Challenges in cancer self-management of patients with limited English proficiency - Fang-Yu Chou; Lily Y Kuang; Jeannette Lee; Grace J Yoo; Lei-Chun Fung (Elsevier, 2016)
Objective: This paper summarizes the barriers and challenges in cancer care reported from a validation project of a self-management intervention handbook from Chinese-American cancer patients with limited English proficiency (LEP). Methods: Seven health-care providers (HCPs) and 16 Chinese-American cancer survivors with LEP were invited to validate a self-management intervention handbook through networking sampling method. Bilingual versions were developed and validated using the repeated translation process. Online and paper-based survey and interview were conducted to collect information on the perception of barriers and experiences on cancer care. Data were analyzed by the content analysis method. Results: The HCPs reported a bilingual self-management handbook which is useful and feasible for patient self-management. The challenges in giving cancer care to LEP patients included: patients do not engage in discussion, different cultural health beliefs, unable to speak to patients in their primary language, and patients are less likely to discuss emotional and social challenges during treatments. The common barriers and experiences during cancer care included: limited understanding about treatment/medication and side effects, language barriers such as unable to communicate to make the decision, unable to understand information related to resources and do not know what questions to ask, and do not know what to expect during their cancer treatment. Conclusions: The current findings highlight the need of cancer self-management support for culturally diverse LEP cancer patients. Further research can include applying the supportive intervention to all LEP cancer patients.